The Important of Streamer’s Attractiveness, Influencer, and Customer Review in Purchasing Decision on TikTok Live - Rosiana, Adilla Salsabella Putri; Mangifera, Liana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: TikTok become one of the most popular social media not only in Indonesia but also globally. Now days TikTok not only utiliziedwatching video but also for conducting transactions, including buying and selling throug TikTok shop and TikTok Live. This study focus on the influence of streamers' attractiveness and influencers on customers' purchasing decisions on TikTok live streaming through online customer reviews as the mediator. Methodology: This research employs quantitative methods, utilizing a probability sampling approach specifically through simple random sampling. The data collection process involves distributing questionnaires through Goggle Form. The study focuses on 150 active students of UMS and UNS. The data analysis method employed is Partial Least Square (PLS), facilitated by SMARTPLS 3.0 software, encompassing both Outer and Inner model analyses. Results: The research results indicate that online customer reviews and streamer’s attractiveness have a significantly positive influence on purchasing decisions. In addition, the streamer's attractiveness and influencers supported influence online customer reviews. online customer reviews fully mediate the influence of influencers on purchasing decisions. streamer's attractiveness in live advertising media is crucial to attract consumers. However, influencer does not supported on purchasing decision. Applications/Originality/Value selecting influencers with good credibility and in-depth knowledge of the products.